2022
DOI: 10.1002/pssr.202100647
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Nucleation and Growth of Single Monolayers in Nanowires: Towards a Deterministic Regime

Abstract: The vapor–liquid–solid growth of semiconductor nanowires proceeds via the sequential nucleation and extension of biatomic monolayers at the interface between the solid wire and a liquid catalyst nanodroplet. In the case of III–V compounds, this mother phase contains only a small concentration of the volatile group V atoms. The growth regime where there is not enough such atoms available in the liquid at nucleation to complete a whole monolayer is studied experimentally and theoretically. Each monolayer cycle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 50 publications
(135 reference statements)
1
13
0
Order By: Relevance
“…During the step-flow process the layer advanced across the LS interface by incrementally filling large sections of the LS interface switching between convex, concave and straight edged configurations (see video S1). This should not be viewed as a lack of temporal resolution of our system, since this type of step-flow behaviour is consistent with previous in-situ studies of nanowire growth [22][23][24] . Images and 2D schematic contours of the faceting of the bilayer for a nanowire not included in the main dataset are shown in Supporting Information SI-3.…”
Section: Fig 1 Incubation In Gaas Nanowires (A-b) Hrtem Images and Sc...supporting
confidence: 87%
See 2 more Smart Citations
“…During the step-flow process the layer advanced across the LS interface by incrementally filling large sections of the LS interface switching between convex, concave and straight edged configurations (see video S1). This should not be viewed as a lack of temporal resolution of our system, since this type of step-flow behaviour is consistent with previous in-situ studies of nanowire growth [22][23][24] . Images and 2D schematic contours of the faceting of the bilayer for a nanowire not included in the main dataset are shown in Supporting Information SI-3.…”
Section: Fig 1 Incubation In Gaas Nanowires (A-b) Hrtem Images and Sc...supporting
confidence: 87%
“…This behaviour has been attributed to the low amount of As atoms in the droplet which is smaller than the amount of As atoms required to cover the whole LS interface 18 . In modelling this phenomenon has been termed the stopping effect, where it was shown that the amount of initial LS interface coverage was strongly dependent on the As flow 24,30,31 . Contrary to incubation time, our data shows that the step-flow time increases for decreasing nanowire diameter across the examined diameter range, as seen in Fig.…”
Section: Fig 1 Incubation In Gaas Nanowires (A-b) Hrtem Images and Sc...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted previously that the depletion which follows the nucleation and the rapid expansion of the island at the interface leads to an antibunching of the nucleation process. The characteristics of this depletion were analyzed further for a low incident flux due to the quantitative approach which can be developed for the VLS growth of III–V nanowires. In this case, a basic process is thought to consist of two steps: (1) the increase of the concentration of group V atoms in the droplet until random nucleation and rapid expansion of the island fed by the excess of concentration and (2) a final expansion to the full ML controlled by the incoming flux.…”
Section: Discussionmentioning
confidence: 99%
“…As the nucleation of the steps is a random process, it raises the question of antibunching, particularly if the velocity of the steps is large, so that the propagation time is much shorter than the nucleation time. More recent studies have focused on the role of the postnucleation period, where the step propagation may be limited by refilling. …”
mentioning
confidence: 99%